2013
DOI: 10.1016/j.devcel.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

WT1 Maintains Adrenal-Gonadal Primordium Identity and Marks a Population of AGP-like Progenitors within the Adrenal Gland

Abstract: SUMMARY Adrenals and gonads share a common primordium (AGP), but the molecular events driving differentiation are poorly understood. Here we demonstrate that the Wilms’ tumor suppressor WT1 is a key factor defining AGP identity by inhibiting the steroidogenic differentiation process. Indeed, ectopic expression of WT1 precludes differentiation into adreno-cortical steroidogenic cells by locking them into a progenitor state. ChIP experiments identify Tcf21 and Gli1 as direct targets of WT1. Moreover, cell lineag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 46 publications
4
111
1
6
Order By: Relevance
“…We extracted expression levels of a list of 28 genes expressed or functionally linked to the progenitor compartment and found that 18 of them were significantly (t test, adjusted P < 0.05) downregulated in Prkar1a-knockout adrenals compared with WT adrenals (Supplemental Figure 4B). We further confirmed by qPCR that Prkar1a ablation in steroidogenic cells resulted in the downregulation of all stem/progenitor markers (12,14,(41)(42)(43) from either capsular or subcapsular compartments (Supplemental Figure 4C). The SHH and RSPO/WNT/β-catenin signaling pathways play an essential role in adult cortex maintenance and renewal (12,14).…”
Section: Pka-dependent Accelerated Cortex Renewal Is Counteracted By supporting
confidence: 54%
“…We extracted expression levels of a list of 28 genes expressed or functionally linked to the progenitor compartment and found that 18 of them were significantly (t test, adjusted P < 0.05) downregulated in Prkar1a-knockout adrenals compared with WT adrenals (Supplemental Figure 4B). We further confirmed by qPCR that Prkar1a ablation in steroidogenic cells resulted in the downregulation of all stem/progenitor markers (12,14,(41)(42)(43) from either capsular or subcapsular compartments (Supplemental Figure 4C). The SHH and RSPO/WNT/β-catenin signaling pathways play an essential role in adult cortex maintenance and renewal (12,14).…”
Section: Pka-dependent Accelerated Cortex Renewal Is Counteracted By supporting
confidence: 54%
“…In the absence of Wt1, high Sf1 expression is induced by an unknown factor, which leads undifferentiated somatic cells to develop into steroidogenic cells. Interestingly, a recent study also showed that the differentiation of steroidogenic cells in the adrenal gland is repressed by Wt1 (Bandiera et al, 2013), implying that Wt1 plays a role in the differentiation of gonad somatic cells, most likely by inhibiting the development of steroidogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The adrenal capsule consists of mesenchymal cells that are positive for the SHH mediator GLI1 (King et al 2009) and COUPTFII (also known as NR2F2) (Wood et al 2013) and surrounded by a thin layer of mesothelial lining expressing the Wilms tumor suppressor WT1 (Bandiera et al 2013). To determine whether Rspo1 and Rspo3 are expressed in the same cell population, we performed cell-sorting experiments on dissociated adult adrenals from Wt1-GFP animals (Hosen et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…By embryonic day 12.5 (E12.5) in mice, the developing organ becomes surrounded by condensing mesenchymal cells that ultimately form the capsule (Bandiera et al 2013). A second contribution to the capsule is likely derived from adrenal progenitor cells that have lost SF1 expression (Wood et al 2013).…”
mentioning
confidence: 99%